An all-Poland survey of physical activity and sedentary lifestyles for middle school, high school and university students - Wojtyła-Buciora, Paulina; Bołdowski, Tomasz; Wojtyła, Cezary; Żukiewicz-Sobczak, Wiola; Juszczak, Katarzyna; Łabędzka-Gardy, Maria; Wojtyła, Andrzej; Krauss, Hanna (Journal of Health Inequalities, 2017)
Introduction: Most countries have witnessed an increasingly sedentary lifestyle in recent decades. Experts estimate that only one third of adolescents undertake sufficient physical activity to guarantee normal physical, mental and emotional development. Study aims: To determine the frequency of PE (Physical Education) lessons as well as after-school movement activities and sedentary behaviour. To establish the association between physical activity, TV watching and computer use (screen time) with the risks of overweight and obesity in students. Material and methods: A survey of 3,548 middle school students, 4,423 from high school and 5,595 university students was performed in 2011. In the former two groupings, the questionnaire had been devised by Poland’s GIS (Chief Sanitary Inspectorate), based on one previously employed for WHO global school-based student health survey (GSHS) studies. The university students used an electronic questionnaire made available on an internet site from Lublin, Poland. Results: Half the middle and high school students undertook 2 to 5 hours of physical activity per week, while only 16% of university students did so. In their free time after school, one quarter of middle and high school students engaged in selected sporting activities, usually for one hour each week. Of the university students, 84% did not undertake any movement activities at all. Excessive body mass was most frequently found in students spending 3 to 4 hours per day watching TV or using computers. Conclusions: Students, in particular at the university level, demonstrated a somewhat poor commitment to undertaking PE lessons or other movement activities, whilst focusing mainly on sedentary activities.